Pendampingan psikologis dan komunikasi efektif para relawan penyintas kekerasan seksual di Yakesma, Baitussalam, Aceh Besar (Psychological and effective communication assistance for volunteers working with sexual violence survivals at Yakesma, Baitussalam, Aceh Besar) - Rosemary, Rizanna; Khairani, Maya; Azman, Zakirah (Universitas Syiah Kuala, 2023)
Yakesma (Aceh Community Welfare Foundation) in Kajhu Village, Baitussalam District, Aceh Besar, focuses on nurturing management by recruiting foster parents and volunteers to assist groups of abandoned children and, primarily, survivors of sexual violence. Child survivors of sexual violence have experienced deep psychological trauma, which requires continuous psychological assistance. The presence of volunteers is significant in accompanying these survivors so that they can recover from the psychological trauma they have experienced. However, not all volunteers have psychological abilities and practical communication skills. This community service aims to equip Yakesma volunteers with the two abilities needed to help themselves when interacting with survivors of sexual violence to recover from their mental health issuesthe community service through workshop and practicum methods. The results of psychological assistance and effective communication received a positive response from the volunteers, encouraging them to write their stories as self-healing. The outputs of community service are training modules and an anthology book of volunteer stories that can be referenced to assist survivors of sexual violence in other institutions.